Suppliers management tactics as a concept of sustainable enterprise development - O. P. Krasyuk (Литьë и металлургия)
The article deals with issues related to the work of OJSC “BSW Management Company of the Holding “BMC” with suppliers. Information on the developed concept of stakeholders between supplier and consumer is given. The types and structure of the procurement process are described, the gradation of the material in the procurement process is carried out. The method of evaluating supplier, starting with the calculation of the quality index of the material supplied, depending on the ratio value of the type of inconsistencies discussed logistics, but also on the basis of partnership relations provides information on the assessment of loyalty of the supplier. The report is also based on the developed activities, 8D, i.e. 8 step-by-step actions to eliminate inconsistencies. Perception of the supplier-consumer relationship is evaluated.